The Bethe-Ansatz approach to the N $$ \mathcal{N} $$ = 4 superconformal index at finite rank - Alfredo González Lezcano; Junho Hong; James T. Liu; Leopoldo A. Pando Zayas (Journal of High Energy Physics, 2021)
Abstract We investigate the Bethe-Ansatz approach to the superconformal index of N $$ \mathcal{N} $$ = 4 supersymmetric Yang-Mills with SU(N) gauge group in the context of finite rank, N. We explicitly explore the role of the various types of solutions to the Bethe-Ansatz Equations in recovering the exact index for N = 2, 3. We classify the Bethe-Ansatz Equations solutions as standard (corresponding to a freely acting orbifold T 2/ℤ m × ℤ n ) and non-standard. For N = 2, we find that the index is fully recovered by standard solutions and displays an interesting pattern of cancellations. However, for N ≥ 3, the standard solutions alone do not suffice to reconstruct the index. We present quantitative arguments in various regimes of fugacities that highlight the challenging role played by the continuous families of non-standard solutions.